A Single-Subject Study on the Effectiveness of Applied Behavior Analysis for Managing Sitting Intolerance in Children with ADHD - Azam, Sumbul; Azam, Madiha (ACADEMIA International Journal for Social Sciences, 2025)
The purpose of the study is to apply methods of Applied Behavioral Analysis in an Educational setting. The study applied the technique of Differential Reinforcement of Alternative Behavior (DRA) to reduce and alter the behavior of Sitting Intolerance. The observation was recorded on the basis of Pre-Intervention Phase, Intervention Phase, Post-Intervention Post and Follow-Up Phase. After the Intervention Phase, there is a significant change in the subject’s behavior which can be seen in the graphical representation of the results, Thus, the findings of the study indicated that Differential Reinforcement of Alternative Behavior (DRA) Is an effective technique to reduce and alter the behavior of Sitting Intolerance.